Early-life exposure to perfluorinated alkyl substances modulates lipid metabolism in progression to celiac disease - Lisanna Sinisalu; Partho Sen; Samira Salihovic; Suvi Virtanen; Heikki Hyoty; Jorma Ilonen; Jorma Toppari; Riitta Veijola; Matej Oresic; Mikael Knip; Tuulia Hyotylainen (Elsevier, 2022)
Celiac disease (CD) is a systemic immune-mediated disorder with increased frequency in the developed countries over the last decades implicating the potential causal role of various environmental triggers in addition to gluten. Herein, we apply determination of perfluorinated alkyl substances (PFAS) and combine the results with the determination of bile acids (BAs) and molecular lipids, with the aim to elucidate the impact of prenatal exposure on risk of progression to CD in a prospective series of children prior the first exposure to gluten (at birth and at 3 months of age). Here we analyzed PFAS, BAs and lipidomic profiles in 66 plasma samples at birth and at 3 months of age in the Type 1 Diabetes Prediction and Prevention (DIPP) study (n = 17 progressors to CD, n = 16 healthy controls, HCs). Plasma PFAS levels showed a significant inverse association with the age of CD diagnosis in infants who later progressed to the disease. Associations between BAs and triacylglycerols (TGs) showed different patterns already at birth in CD progressors, indicative of different absorption of lipids in these infants. In conclusion, PFAS exposure may modulate lipid and BA metabolism, and the impact is different in the infants who develop CD later in life, in comparison to HCs. The results indicate more efficient uptake of PFAS in such infants. Higher PFAS exposure during prenatal and early life may accelerate the progression to CD in the genetically predisposed children.